The Healthcare Improvement Scotland evidence note rapid review process: providing timely, reliable evidence to inform imperative decisions on healthcare. Issue 2 (June 2016) - McIntosh, Heather M.; Calvert, Julie; Macpherson, Karen J.; Thompson, Lorna
ABSTRACT: Aim: Rapid review has become widely adopted by health technology assessment agencies in response to demand for evidence-based information to support imperative decisions. Concern about the credibility of rapid reviews and the reliability of their findings has prompted a call for wider publication of their methods. In publishing this overview of the accredited rapid review process developed by Healthcare Improvement Scotland, we aim to raise awareness of our methods and advance the discourse on best practice. Methods: Healthcare Improvement Scotland produces rapid reviews called evidence notes using a process that has achieved external accreditation through the National Institute for Health and Care Excellence. Key components include a structured approach to topic selection, initial scoping, considered stakeholder involvement, streamlined systematic review, internal quality assurance, external peer review and updating. Results: The process was introduced in 2010 and continues to be refined over time in response to user feedback and operational experience. Decision-makers value the responsiveness of the process and perceive it as being a credible source of unbiased evidence-based information supporting advice for NHSScotland. Conclusion: Many agencies undertaking rapid reviews are striving to balance efficiency with methodological rigour. We agree that there is a need for methodological guidance and that it should be informed by better understanding of current approaches and the consequences of different approaches to streamlining systematic review methods. Greater transparency in the reporting of rapid review methods is essential to enable that to happen.